Playing with Formulas - Gethin, Rupert (Indo-Iranian journal, 2025)
This article considers three recent monographs (Allon 2o21, Shulman 2021, Anālayo 2022) concerned with the composition and transmission of early Buddhis texts. While these texts are generally accepted as composed and initially transmitted orally, three issues emerge as contested by the authors: (1) how far the variations in language, wording and arrangement are indicative of a period of relatively free oral composition and transmission during which the texts remained unfixed; (2) the role of repeated formulas in oral composition and transmission; and (3) whether the texts are better regarded as compilations of textual memories of the Buddha and his teachings or as deliberate literary compositions. The article argues that neither the kinds of variation we find between different versions of texts (surviving in Pali, Buddhist Sanskrit, Gāndhāri, and Chinese translation) nor the aspects of literary construction presented by the texts are adequately accounted for by Anālayo’s theory of layered ‘textual memories’; these require something close to the Parry-Lord theory of oral literature (as first proposed by Lance Cousins) and Shulman’s notion of ‘the play of formulas’.